Monitoring surface oscillation dynamics of tropical peatlands: a novel approach using APSIS-InSAR - Ledger, Martha (2022)
80% of tropical peatland in Indonesia and Malaysia (15% of Earth's soil carbon) is drained for production of pulpwood and palm oil. Associated increases in peat decomposition and large-scale forest fires have led to widespread subsidence and deterioration of peat condition. However, quantification of subsidence and peat condition from these processes across SE Asia is challenging due to the scale and inaccessibility of dense tropical peat swamp forests.